1959
DOI: 10.1001/archpedi.1959.02070010389004
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Granulomatous Disease of Childhood

Abstract: In 1950, a 12-month-old child was referred to the University of Minnesota Hospitals with a syndrome consisting of chronic suppurative lymphadenitis, hepatosplenomegaly, pulmonary infiltrations, and an eczematoid dermatitis about the eyes, nose, and mouth. Since then we have seen three other children with an almost identical clinical picture. This syndrome appears to be a distinct clinical entity not previously described in the medical literature. This durated matted lymph nodes were still present in the inguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

1966
1966
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(38 citation statements)
references
References 14 publications
(1 reference statement)
2
34
0
2
Order By: Relevance
“…It was demonstrated that the leukocytes of all eight mothers and several sisters were intermediate in bactericidal capacity and tetrazolium reduction between leukocytes of affected boys and controls. This demonstration of female carriers indicates the sex-linked character of chronic granulomatous disease and adds considerable weight to the earlier suggestion that chronic granulomatous disease is inherited in a sex-linked manner (10,12). These genetic data are certainly a sound indication that a single enzyme is lacking or deficient in the leukocytes of patients with this disease.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It was demonstrated that the leukocytes of all eight mothers and several sisters were intermediate in bactericidal capacity and tetrazolium reduction between leukocytes of affected boys and controls. This demonstration of female carriers indicates the sex-linked character of chronic granulomatous disease and adds considerable weight to the earlier suggestion that chronic granulomatous disease is inherited in a sex-linked manner (10,12). These genetic data are certainly a sound indication that a single enzyme is lacking or deficient in the leukocytes of patients with this disease.…”
Section: Discussionsupporting
confidence: 73%
“…A chronic fatal granulomatous disease of childhood has been separated from the many granulomatous diseases of childhood and defined as a clinical entity by Berendes et al (9) and Bridges 1422 et al (10). This disease is characterized by apparent sex-linked inheritance, increased frequency of infections, chronic suppurative and granulomatous lymphadenitis, parenchymatous granulomatous infiltrations, and episodes of infected and eczematoid dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…3 is a primary immunodeficiency disorder caused by inherited defects in the NADPH oxidase complex (1)(2)(3). This enzyme complex is used by phagocytic cells to generate microbicidal superoxide and its metabolites hydrogen peroxide, hydroxyl anion, and hypohalous acid (4).…”
Section: Hronic Granulomatous Disease (Cgd)mentioning
confidence: 99%
“…We conclude from our results that the deficiency in oxygen metabolism by CGD cells does not affect antigen processing and presentation either by macrophages, dendritic or B cells. This explains the normal synthesis of antibodies to tetanus toxin and other antigens in these patients after vaccination [26].…”
Section: Discussionmentioning
confidence: 76%